1996
DOI: 10.2307/2082611
|View full text |Cite
|
Sign up to set email alerts
|

“Race Coding” and White Opposition to Welfare

Abstract: Crime and welfare are now widely viewed as “coded” issues that activate white Americans' negative views of blacks without explicitly raising the “race card.” But does the desire of whites to combat crime or curtail welfare really stem from their dislike of blacks? Are these not pressing problems about which Americans rightly should be concerned—apart from any associations these issues may have with race? In this paper I assess the extent to which white Americans' opposition to welfare is rooted in their attitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
345
1
10

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 414 publications
(381 citation statements)
references
References 29 publications
19
345
1
10
Order By: Relevance
“…United States Using data from the 1986 National Election Study, the 1994 General Social Survey, and the 1991 National Race and Politics Study, Gilens (1995Gilens ( , 1996Gilens ( , 1999 shows that racial stereotypes are important predictors of the support for welfare spending among white Americans. 4 Moreover, Gilens (1999) documents that black people are overrepresented in the media coverage of poverty, and in particular in the least sympathetic stories.…”
mentioning
confidence: 99%
“…United States Using data from the 1986 National Election Study, the 1994 General Social Survey, and the 1991 National Race and Politics Study, Gilens (1995Gilens ( , 1996Gilens ( , 1999 shows that racial stereotypes are important predictors of the support for welfare spending among white Americans. 4 Moreover, Gilens (1999) documents that black people are overrepresented in the media coverage of poverty, and in particular in the least sympathetic stories.…”
mentioning
confidence: 99%
“…Martin Gilens (1996) found that-among ideology and other personal characteristics-racial attitudes were the most salient explanation of whites' positions on welfare policy. Through this lens, the reasoning behind some residents' opposition to the Mayor's plan, such as increased crime or loitering around the proposed shelter sites, can be viewed as coded statements that reflect longstanding racial stereotypes.…”
Section: Neighborhood Oppositionmentioning
confidence: 99%
“…In these cases, the metaphor presents racial discourse as a "trump" card that boldly attempts to "win a hand." "Playing the race card" also refers to insinuations or coded references that may signify race, but are meant to be undetectable as "racial," such as "urban," "welfare," or "inner city" (Gilens, 1996;Lee & Morin, 2009). Political "conservatives" are often said to play on race either to trivialize racial discourse or to provoke white voters through implicit racial fears (Mendelberg, 2001).…”
Section: Trumping Tropes With Joke(r)smentioning
confidence: 99%